2018
DOI: 10.1080/07357907.2018.1434539
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Vaccine-Strain Measles and Mumps Viruses Enhances Oncolytic Activity against Human Solid Malignancies

Abstract: Oncolytic measles and mumps viruses (MeV, MuV) have a potential for anti-cancer treatment. We examined the anti-tumor activity of MeV, MuV, and MeV-MuV combination (MM) against human solid malignancies (HSM). MeV, MuV, and MM targeted and significantly killed various cancer cell lines of HSM but not normal cells. MM demonstrated a greater anti-tumor effect and prolonged survival in a human prostate cancer xenograft tumor model compared to MeV and MuV. MeV, MuV, and MM significantly induced the expression of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 26 publications
5
29
0
Order By: Relevance
“…During the last decade, the fast extension of global OVs research resulted in benefits to the population. Son et al [ 81 ] revealed the combination of OVs with various therapies leads to improved infection efficiency and increased antitumor effects. They suggested that the cytopathic effects of measles and mumps viruses’ combination (MM) can improve the antitumor activity and tumour cell killing in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, the fast extension of global OVs research resulted in benefits to the population. Son et al [ 81 ] revealed the combination of OVs with various therapies leads to improved infection efficiency and increased antitumor effects. They suggested that the cytopathic effects of measles and mumps viruses’ combination (MM) can improve the antitumor activity and tumour cell killing in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This feature makes MuV a desirable candidate for the treatment of various cancers. Accordingly, different strains of MuV, derived from different isolates, have been examined as OVs (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have been recently conducted in this area. More recently, however, some natural and chimeric MuV strains have been studied as potential anti-cancer agents (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, remission was also observed in syngeneic TRAMP-C subcutaneous tumors and after intravenous vector administration in PC-3M-Luc bone metastases. In a combination therapy approach, oncolytic MV and mumps virus (MuV) vectors were evaluated in a human prostate cancer xenograft model [ 128 ]. Greater anti-tumor effect and prolonged survival were obtained from combination therapy compared to individual treatment either with MV or MuV vectors.…”
Section: Vaccines Against Cancermentioning
confidence: 99%